Assessment of Safety Culture in Tertiary Institutional Chemical Analytical Laboratories in Oghara and Warri, Delta State, Nigeria - Agaja, S. A.; Birma, G. J.; Ndu , C. J. (Cutting Edge Research in Biology Vol. 2, 2022)
The objective of this study was to assess the safety culture in 20 chemical analytical laboratories in the Nigerian Delta state towns of Oghara and Warri. This was achieved through a determination of the safety performance between tertiary education chemical laboratories and industrial laboratories, private and government-owned laboratories, and technical and non-technical labs. The 5-point Likert scale questionnaire and a common checklist were the research methods used in this study. A t-test comparison of private and government-owned laboratories revealed that the safety culture of private-owned laboratories, regardless of whether they were industrial or higher education, was more significant (P < 0.05) than that of government-owned laboratories. Analysis of t-test for the survey indicated no significant difference between tertiary education and industrial laboratories (P > 0.05), with a mean value of 3.69798 for tertiary education laboratories and 3.62842 for industrial laboratories. Analysis of t-test also indicated P < 0.05 for technical (M = 75.00) and non-technical (M = 56.11) tertiary education laboratories. The overall mean for tertiary education chemical analytical laboratories is 67.90, which is higher than the overall mean for industrial chemical analysis laboratories, which is 54.50. It is advised that laboratories set up a departmental safety committee-led internal review mechanism for events and corrective actions, and hold recurring safety seminars on the lessons that can be gained from accidents. All analytical laboratories should also implement a strong and effective safety management system.